Report on Some Terrestrial Molluscs from Different Regions of Nepal - Subba, Bharat Raj; Ghosh, Tapan Kumar (Journal of Natural History Museum, 2009)
Nine species of terrestrial molluscs were collected at eastern, mid western and far western regions of Nepal. The documented molluscan samples are represented with 4 families under three orders. Out of the total record of nine species, four species belonged to the family Ariophantidae, three species to Subulinidae, one species to Bradybaenidae and one to Veronicellidae. Key Words: Molluscs; Nepal; record; species; terrestrial Journal of Natural History Museum Vol. 23, 2008 Page 78-81